(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
The development of biomedical engineering in recent decades has led to a revolution in the development of prosthetics for people with disabilities. The field of prosthetics for sensory organs, however, has proven a challenge for scientists, who are faced with the problem of discovering how the body perceives the signals coming from the outside world and transforms them to be assimilated by our brain. Within this field lie cochlear implants which, although still far from having a perfect performance, have evolved surprisingly thanks to the efforts of researchers, and today provide millions of people around the world the possibility to listen and communicate. This article aims to briefly review the basic concepts involved in the function of the auditory system and how cochlear implants work.